Exploring students experiences of receiving e-formative feedback during emergency remote learning: A case study of first-year students at a teacher education university in South Africa - Simelane, Raudina Madina (University of the Witwatersrand, Johannesburg, 2024)
The COVID-19 pandemic necessitated an abrupt transition to Emergency Remote Teaching and Learning (ERT&L) across the higher education landscape globally, including teacher education programs in South Africa. This seismic shift profoundly disrupted conventional assessment approaches dependent on face-to-face teaching and continuous formative assessments. Consequently, instructors were compelled to reconceptualise formative assessment for the realities of remote learning, adopting digital tools to administer e-assessments and provide e-formative feedback. Concurrently, first- year student teachers faced monumental challenges accessing and productively responding to digitally-mediated formative feedback amidst the isolating remote context lacking traditional supports. Against this backdrop, this qualitative case study explored the lived experiences of thirty- six first-year Bachelor of Education students receiving e-formative feedback through a university’s Canvas Learning Management System during ERT&L conditions in South Africa. Framed by an interpretive paradigm combining Social Constructivist, Feedback Intervention, and Feedback Design theoretical tenets, the study aimed to explore how students perceived and engaged with e-formative feedback to facilitate their self- regulated remote learning. Through Thematic Analysis of semi-structured interviews and focus group discussions, findings unveiled diverse student realities shaped by multifaceted technological, cognitive, and motivational barriers. Prominent obstacles included lack of digital access, connectivity issues, deficient computer literacy skills, and unfamiliar vocabulary – factors impeding feedback reception. Moreover, untimely and unspecific feedback further undermined its value, with many students prioritising marks over substantive comments. Ultimately, suboptimal design coupled with insufficient feedback literacy and self-regulation capacities among this vulnerable population severely constrained productive feedback engagement and autonomous learning progress during the emergency transition. This study’s findings highlight the need for reconceptualised e-formative feedback approaches that holistically account for technological equity gaps, targeted skills development, and psychosocial support mechanisms to foster meaningful feedback utilisation during disruptions. Crucially, it calls for elevating student voices to better understand their contextualised needs, informing responsive interventions. Emergent insights illuminate opportunities to enhance digital feedback literacy, diversify feedback modes, accelerate feedback turnaround, and nurture conducive ecosystems where first- year students thrive as empowered, self-regulating learners even amid crises. Such learner-centric innovations have lasting relevance for optimising equitable, sustainable assessment design across evolving educational futures.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Emergency Remote Learning; e-formative feedback; accessibility; specificity; emotionality; timing; valence; self-regulated learning; Social Constructivism; Feedback Intervention Theory; Feedback Design Theory; SDG-4: Quality education